Measurements of 3ΛH and 4ΛH Lifetimes and Yields in Au+Au Collisions in the High Baryon Density Region - Abdallah, Mohamed Samy; Deppner, Ingo Martin; Herrmann, Norbert; Söhngen, Yannick; Weidenkaff, Philipp (Physical review letters, 2022)
We report precision measurements of hypernuclei 3ΛH and 4ΛH lifetimes obtained from Au+Au collisions at √sNN=3.0 GeV and 7.2 GeV collected by the STAR experiment at the Relativistic Heavy Ion Collider, and the first measurement of 3ΛH and 4ΛH midrapidity yields in Au+Au collisions at √sNN=3.0 GeV. 3ΛH and 4ΛH, being the two simplest bound states composed of hyperons and nucleons, are cornerstones in the field of hypernuclear physics. Their lifetimes are measured to be 221±15(stat)±19(syst) ps for 3ΛH and 218±6(stat)±13(syst) ps for 4ΛH. The pT-integrated yields of 3ΛH and 4ΛH are presented in different centrality and rapidity intervals. It is observed that the shape of the rapidity distribution of 4ΛH is different for 0%-10% and 10%-50% centrality collisions. Thermal model calculations, using the canonical ensemble for strangeness, describes the 3ΛH yield well, while underestimating the 4ΛH yield. Transport models, combining baryonic mean-field and coalescence (jam) or utilizing dynamical cluster formation via baryonic interactions (phqmd) for light nuclei and hypernuclei production, approximately describe the measured 3ΛH and 4ΛH yields. Our measurements provide means to precisely assess our understanding of the fundamental baryonic interactions with strange quarks, which can impact our understanding of more complicated systems involving hyperons, such as the interior of neutron stars or exotic hypernuclei.
Gesehen am 21.07.2022
Im Titel sind die Zahlen 3 und 4 hochgestellt